Hamburg : The Monocle Travel Guide Series - Monocle, ....- (Gestalten : Berlijn, 2019)
If Berlin is Germany's clubbing capital then Hamburg is the dinner party that's as raucous as it is refined - and the guests are a varied bunch too. Stroll around this prosperous port city and you'll brush shoulders with local fishermen casting their nets on the banks of the River Elbe, world- renowned gallerists hosting exhibitions by cutting-edge artists, and independent retailers flaunting wares that are either "Made in Hamburg" or highly exotic. We've picked out our preferred spots in which to wine and dine, whether you're after a snifter in the hinterland of the red-light district or a Fischbrötchen on the wind-whipped docks. We've highlighted the architectural landmarks that reflect the city's rich history and bright future, including the red-brick buildings that survived the Second World War and the up-and-coming HafenCity's gleaming towers. When you're ready to rest your head, look no further than our round-up of the best hotels - a grande dame with a private boat to ferry you to and from an evening at the Elbphilharmonie, anyone? You can also find a paddleboarding class or two to blow away the cobwebs the following morning. Hamburg is a historic but forward-thinking city, home to arbiters of tradition and avant garde artists alike. Ready? It's time to pull up a chair and meet the lot of them.
Keywords: Hamburg; Reisgids